KEY FACTORS IN THE LIFE CYCLE OF PERUVIAN FAMILY BUSINESSES - Cáceres Alemán, Pedro Luis (2024)
Objective: Identify and analyze the key factors in the life cycle of Peruvian family businesses. Material and methods: A quantitative and qualitative research was carried out, with a descriptive and explanatory scope, non-experimental, with a cross-sectional and correlational design. The sample consisted of 10 Peruvian family businesses in the service, commercial, and industrial sectors, to which a survey consisting of 9 sections with 67 questions was applied in November 2021. Likewise, the information collected was processed and analysed using the SPSS 25 software. Results: The results, from the primary and secondary information that was collected, showed that Peruvian family businesses are characterized by low levels of professionalization and corporate governance, even though they are These are some of the main factors that significantly influence the life cycle of this type of company. Conclusion: Key factors such as professionalization, the preparation of a succession plan, family protocol, good communication and teamwork, as well as good corporate governance, significantly influence the life cycle of Peruvian family businesses, in consideration of the particularities and different challenges that each one of them goes through.